CHALLENGES OF JKN MOBILE APPLICATION UTILIZATION IN THE BPJS PATIENT REGISTRATION PROCESS AT X HOSPITAL: A CASE STUDY IN X HOSPITAL - Jimmy S., Rifdinia Bregita; Ratri, Devita Rahmani; Harjayanti, Nofita Dwi (Universitas Brawijaya, 2025)
The JKN mobile application (MJKN), is an application presented by BPJS with the aim of providing convenience for its participants. MJKN utilization in registration process is one of the BPJS compliance indicators for hospitals. As part of BPJS partners, the achievement of compliance indicators is something that must be achieved by Hospital X. Until September 2024, the highest rate of MJKN utilization in X Hospital was 21% of the target achievement of ≥30%. This study aims to determine the challenges and barriers of fulfilling the MJKN utilization indicators in registration process at X Hospital. This research is a qualitative research with a case study approach. In-depth interviews were conducted with eight BPJS patients and eight people from X Hospital management related to the implementation of MJKN. Data analysis is strengthened by triangulating based on observations and secondary data related to the MJKN process. Seven challenges were identified, including the low quality of evaluation of staff performance at Hospital X related to MJKN, the difficulty of bridging between hospital information system and the MJKN information system, patient difficulties during the MJKN account registration process, low access to information related to MJKN, the complexity of the MJKN check in process, resistance to technology, and patient devices that do not meet MJKN standards. The results of this study can be the basis for Hospital X management in determining solutions to improve the achievement of MJKN utilization.